Splicing in the Diagnosis of Rare Disease: Advances and Challenges - Lord, Jenny; Baralle, Diana (Frontiers in Genetics, 2021)
Mutations which affect splicing are significant contributors to rare disease, but are frequently overlooked by diagnostic sequencing pipelines. Greater ascertainment of pathogenic splicing variants will increase diagnostic yields, ending the diagnostic odyssey for patients and families affected by rare disorders, and improving treatment and care strategies. Advances in sequencing technologies, predictive modelling and understanding of the mechanisms of splicing in recent years pave the way for improved detection and interpretation of splice affecting variants, yet several limitations still prohibit their routine ascertainment in diagnostic testing. This review explores some of these advances in the context of clinical application, and discusses challenges to be overcome before these variants are comprehensively and routinely recognised in diagnostics.